2005
DOI: 10.1097/01.mlg.0000160528.50017.3c
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Controlled Clinical Trial of a Novel Matrix Hemostatic Sealant in Patients with Acute Anterior Epistaxis

Abstract: Floseal hemostatic sealant is a better tolerated, more effective, safe, and easy alternative to nasal packing in patients presenting with acute anterior epistaxis. Future studies may wish to evaluate Floseal's use in posterior epistaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 12 publications
3
84
2
1
Order By: Relevance
“…Common absorbable materials used for anterior packing include oxidized cellulose (e.g., Surgicel, Johnson & Johnson, New Brunswick, NJ, USA) and gelatin foams (e.g., Gelfoam, Pfizer, New York, NY, USA). Another product that combines thrombin with gelatin (e.g., Floseal, Baxter Health Care Corp, Deerfield, IL, USA) is used as a highviscosity gel for hemostasis (19). All these absorbable products are easily used and cause minimal pain and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Common absorbable materials used for anterior packing include oxidized cellulose (e.g., Surgicel, Johnson & Johnson, New Brunswick, NJ, USA) and gelatin foams (e.g., Gelfoam, Pfizer, New York, NY, USA). Another product that combines thrombin with gelatin (e.g., Floseal, Baxter Health Care Corp, Deerfield, IL, USA) is used as a highviscosity gel for hemostasis (19). All these absorbable products are easily used and cause minimal pain and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…The use of FloSeal in cardiac [9], vascular [10,11], urological [12][13][14][15], lacrimal [16], neurosurgical [17], experimental [18], and nasal/sinus [19][20][21][22][23][24] surgery has been widely reported in the literature. However, only one study using FloSealmatrix hemostatic agent in thyroid surgery has been reported to date, and this was an uncontrolled study [25].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 60 % of the populations are affected by [13,14]. Several medical and hemostatical agents can be used to manage epistaxis, including the vasoconstrictor agents' cocaine, oxymetazoline, xylometazoline, and phenylephrine [14][15][16]. Ensuring a secure airway and hemodynamic stability is important for the management of epistaxis.…”
Section: Discussionmentioning
confidence: 99%